Spin-Off and Innovation in the Pharmaceutical Industry. (6th November 2014) - Peruffo, Enzo; Pirolo, Luca; Nenni, Maria Elena
Parent companies usually undertake corporate spin-offs to cope with higher competitive environments or when, in high technology industries, the differences between R&D investments and intangible assets are larger. Consistent with the recent "positive view", spin-offs can be considered as a "proactive strategic choice" to foster innovation, develop new activities, being different from past strategic initiatives and, more generally, not being strictly connected to the corporate strategy of the firm. In order to investigate the relation between divestiture decisions and innovation, we conduct an explorative case study in the pharmaceutical industry to show how spin-offs can help firms to explore new opportunities for innovation, search for new funding and push to create the basis for future development.